Electroacupuncture Improves Neurobehavioral Function Through Targeting of SOX2-Mediated Axonal Regeneration by MicroRNA-132 After Ischemic Stroke - Zhao, Xiaoying; Bai, Fuhai; Zhang, Erfei; Zhou, Dandan; Jiang, Tao; Zhou, Heng; Wang, Qiang (Frontiers in Molecular Neuroscience, 2018)
Our previous studies have shown that electroacupuncture (EA) enhances neurobehavioral functional recovery after ischemic stroke, however, the underlying regulatory mechanisms remain unclear. MicroRNAs (miRNAs) are abundant in the brain and are involved in post-transcriptional gene regulation. During cerebral ischemia reperfusion, miRNAs perform numerous biological functions in the central nervous system related to regeneration and repair of damaged nerves. Our previous studies also have shown that the expression of miRNA-132 (miR-132) is obviously down-regulated after stroke by middle cerebral artery occlusion (MCAO), which can be up-regulated by EA. This study aimed to identify whether up-regulation of miR-132 by EA improved the damaged nerves after stroke and to screen the potential target of miR-132. The results showed that EA up-regulated miR-132 thus suppressing SOX2 expression in vivo after MCAO, which obviously ameliorated neurobehavioral functional recovery. Moreover, our results also suggested that up-regulated miR-132 suppressed SOX2 in primary neurons after oxygen-glucose deprivation (OGD), which promoted neurite outgrowth. In conclusion, EA enhances neurobehavioral functional recovery against ischemic stroke through targeting of SOX2-mediated axonal regeneration by miR-132.